Sustainability and sustainable development in engineering education - Loureiro, Solange Maria; Pereira, Vera Lúcia Duarte do Valle; Pacheco Júnior, Waldemar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
One of the challenges of this century is related to the perspective that the societies become socially, environmentally and economically sustainable in order to satisfy the needs of present generations without reducing the chances of the future generations to achieve theirs. It is through higher education that new professionals start acting, thus, influence how current and future generations deal with the social, environmental and economic issues, i.e., with the sustainability and the Sustainable Development (SD). So, it is responsibility of higher education to provide to the people competencies to enable them to deal with the technical and environmental challenges through solutions that minimize environmental impacts and social inequalities. As the engineers have direct relationship to the production of knowledge and technologies that directly impact society and the environment is essential that the engineering background allows them to design technologies and economic activities to sustain rather than degrade the natural environment and improve health and human well-being. In this context, this paper aims to reflect about the vision of sustainability/DS required for engineering education so that it may contribute to make sustainable societies.